(untitled) (Diametros, 2017)
Researchers doing welfare-related science frequently mischaracterize either situations of decision-theoretic mathematical/scientific uncertainty (defined in terms of purely-subjective probabilities) as situations of risk (defined in terms of reliable, often frequency-based, probabilities), or situations of risk as those of uncertainty. The paper (1) outlines this epistemic/ethical problem; (2) surveys its often-deadly, welfare-related consequences in environmental-health sciences; and (3) uses recent research on diesel particulate matter to reveal 7 specific methodological ways that scientists may mischaracterize lethal risks instead as situations of uncertainty, mainly by using methods and assumptions with false-negative biases. The article (4) closes by outlining two normative strategies for curbing misrepresentations of risk and uncertainty, especially in welfare-affecting science.